Investors’ Interpretations Of Financial Statement Information In Investment Decision Making - Andi Mulia Saleh; Amiruddin; Darmawati (International Journal of Education Management and Religion, 2026)
Financial statements play a crucial role in capital markets by providing information that supports investment decision-making. Despite their importance, investors do not always interpret financial statement information uniformly because interpretation is influenced by individual knowledge, experience, and psychological factors. This study aims to explore how investors interpret financial statement information, identify factors influencing those interpretations, and examine the role of interpretation in investment decision-making. The study employs a qualitative approach within an interpretive paradigm to understand the meanings investors assign to accounting information. Data were collected through in-depth interviews, observations, and documentation involving active capital market investors selected using purposive sampling. Data analysis followed the interactive model of data condensation, data display, and conclusion drawing, complemented by thematic analysis to identify recurring patterns. The findings reveal that investors perceive financial statements as important sources of information for evaluating company performance, profitability, financial stability, and growth prospects. Interpretations vary according to financial literacy, investment experience, information complexity, perceived credibility of financial reports, psychological characteristics, and social influences. Experienced investors tend to interpret accounting information more critically and integrate it with contextual considerations, whereas less experienced investors often depend on external information sources. The findings also demonstrate that investment decisions are not based solely on financial statement information but emerge from an interpretative process involving accounting information, investor characteristics, and broader informational environments. This study contributes to the accounting and behavioral finance literature by demonstrating that financial statements function not only as providers of objective information but also as interpretative instruments through which investors construct meaning and make investment decisions.